Cricothyrotomy in Acute Upper Gastrointestinal Bleed: A Difficult Airway Simulation Case for Anesthesiology Residents - Corinna J. Yu; Frank Rigueiro; Kevin Backfish-White; Johnny Cartwright; Christopher Moore; Sally A. Mitchell; Tanna Boyer (Association of American Medical Colleges, 2024)
Introduction Patients with acute upper gastrointestinal bleeding may have challenging airways. This simulation teaches anesthesiology residents the skill of cricothyrotomy as a surgical last resort while managing acute bleeding in the airway. Methods The simulation involved a 55-year-old patient with history of alcohol abuse admitted to the ICU with hematemesis and acute blood loss for esophagogastroduodenoscopy in the ICU setting. The mannequin had tubing in the posterior oropharynx connected to a pressurized bag of simulated blood hidden from view. While conversing, the patient began to cough and gag, and the bag of fluid was opened, filling the posterior oropharynx with blood, which prompted immediate intubation attempts, designed to fail no matter what the learners attempted. When residents requested a surgical airway, they were provided with a cricothyrotomy kit and a task trainer to perform the procedure. Residents were evaluated using a behavior checklist, debriefed, then asked to complete a postsimulation survey. Results Fifty-eight anesthesiology residents completed the simulation and provided feedback via a 5-point Likert scale of agreement. Most residents quickly recognized the need for emergency intubation. Eighty-eight percent of participants strongly agreed that the simulation was a valuable learning experience, with 99% stating it increased their confidence and clinical decision-making in handling similar scenarios in the future. Discussion This simulation provides a chance to practice valuable airway management skills that increase resident confidence in cricothyrotomy. Future work may examine if these skills and confidence levels are sustainable over time and if they are applied in future patient encounters.